두루누리 사회보험 지원사업의 성과평가와 정책적 시사점; Evaluating the Social Security Subsidy Program in Korea - Dohyung Kim (Korea Development Institute (KDI), 2016)
– Social security subsidies in Korea were introduced in 2012 to reduce the coverage gap in social security. Despite the large fiscal cost, however, the subsidies have only a small effect on the social security coverage: For every 1,000 workers and their employers who are subsidized under the program, the program added just 15 workers covered by social security. Rather than pursuing costly subsidization policies, the Korean government needs to make serious efforts for more efficient collection of social contributions to close the coverage gap in social security. - To reduce the coverage gap in social security, the Korean government began to provide subsidies for the social security contributions of low-wage workers and their employers in small establishments. - The subsidy program matches workers' and employers' contributions to the national pension and the unemployment insurance scheme. - About 0.9 million workers and their employers in 0.5 million establishments were subsidized by the subsidy program in 2015. - For every 1,000 subsidized employees and about 600 subsidized employers, the subsidy program creates only 15 additional covered employees. - Unlike similar active labor market policies adopted in several European countries, the subsidy program had no discernible effect on employment. - The subsidy program can act as a tax rather than a subsidy depending on whether the uncovered worker contributes to the medical insurance scheme. - The subsidy program is contradictory because it gives subsidies for participation in mandated schemes as if it was a choice initially. - A large informal sector with a modest social contribution burden in Korea indicates a sizeable room to enhance administrative efficiency for reducing coverage gap in social security
Keywords: 330